1996
DOI: 10.1291/hypres.19.201
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Activates Endothelial Constitutive Nitric Oxide Synthase via AT1 Receptors.

Abstract: To determine whether angiotensin (ANG) II, a vasoconstrictor hormone, activates constitutive nitric oxide synthase (cNOS) in endothelial cells (ECs), we investigated the cellular mechanism by which ANG II induces nitric oxide (NO) formation in cultured bovine ECs. ANG II rapidly (within 1 min) and dose-dependently (10-9-106 M) increased nitrate/nitrite (NOx) production. This effect of ANG II was abolished by a NOS inhibitor, NG-monomethyl-L-arginine.An ANG II type 1 (AT1) receptor antagonist (DuP 753), but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 23 publications
4
50
2
1
Order By: Relevance
“…Studies on bovine vascular endothelial cells and rat aortic endothelial cells have demonstrated that ANG II can increase the expression and activity of endothelial nitric oxide synthase, leading to increased production of NO (4,32,34). ANG II also increases the expression of cyclooxygenase-2 in human vascular endothelial cells (20), rat ventricular cardiomyocytes (33), and rat vascular smooth muscle cells (31), stimulating production of the vasodilator prostaglandins PGI 2 and PGE 2 (2,33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bovine vascular endothelial cells and rat aortic endothelial cells have demonstrated that ANG II can increase the expression and activity of endothelial nitric oxide synthase, leading to increased production of NO (4,32,34). ANG II also increases the expression of cyclooxygenase-2 in human vascular endothelial cells (20), rat ventricular cardiomyocytes (33), and rat vascular smooth muscle cells (31), stimulating production of the vasodilator prostaglandins PGI 2 and PGE 2 (2,33).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of significant difference in the hypertensive phenotypes of rgs2 heterozygous versus homozygous nulls could result from stimulation of endothelial production of NO or other vasodilatory factors by angiotensin II (39)(40)(41)(42). According to this model, an initial response to angiotensin II would be more robust in rgs2 homozygous nulls than in heterozygous nulls, but blood pressure would not be higher in rgs2 homozygous nulls because they would produce more NO or other vasodilatory factors as a counterbalancing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This vasoconstriction is partly inhibited by Ang II-mediated release of NO from the endothelium. 47,48 Because individuals with the ACE D allele have higher plasma and tissue ACE concentrations, we hypothesized that the D allele of the ACE gene, by increasing local Ang II generation and decreasing bradykinin activity, may modulate vascular tone. 10,49 In the present study, we found no difference in endothelial function in the sedentary subjects according to ACE genotypes, as has been found in other studies.…”
Section: Ace Gene Polymorphism and Endothelial Functionmentioning
confidence: 99%